Assessing teacher competence in gender equality in the Moroccan educational context - Rguibi, Hafid; Tijania, Khalid; Taleme, Naoual (Frontiers in Education, 2025)
IntroductionGender-responsive education plays a crucial role in fostering equitable learning environments. Despite Morocco’s legal and institutional efforts to promote gender equality, the integration of gender-sensitive teaching practices remains inconsistent. This study assesses the attitudes and competencies of Moroccan teaching staff, including trainee teachers, regarding gender-responsive education.MethodsA mixed-methods approach was employed to evaluate gender knowledge and awareness, the application of gender-responsive teaching strategies, and the development of gender-related behaviors. The Teacher’s Gender Equality Competence Scale (TEGEP) was administered to 242 participants, primarily from teacher training institutions. Quantitative data were analyzed using descriptive statistics and correlation analysis to identify key trends and relationships.ResultsThe findings reveal diverse perspectives on gender equality in education. While some participants exhibit strong self-efficacy in applying gender-responsive teaching methods, others demonstrate limited awareness and preparedness. Variations in competency levels are influenced by educational background and teaching experience, highlighting both strengths and areas requiring improvement.DiscussionThese results emphasize the need for targeted professional development programs to strengthen teachers’ gender-responsive competencies. Enhancing both initial training and continuous professional learning is crucial for embedding gender-sensitive pedagogy effectively within Moroccan classrooms.